Pandemi Covid-19, Biaya Pendidikan dan Motivasi Karir dan Minat Melanjutkan Pendidikan Profesi Akuntansi - Ayu Intan Purnama Sari, Anak Agung; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2022)
The purpose of the study was to determine the effect of career motivation and education costs on student interest in continuing their education to the Accounting Profession Education (PPAk) level with the limitations of the Covid-19 pandemic. The research population is accounting students who are taking semester 7 and obtained as many as 251 students as samples. Sampling technique with purposive sampling method. The data analysis technique used was moderated regression analysis. The results of the analysis show that educational costs have a negative effect on student interest in accounting profession education (PPAk), career motivation has a positive effect on student interest in accounting profession education (PPAk), the covid-19 pandemic strengthens the effect of educational costs on interest in accounting profession education (PPAk). ) and the COVID-19 pandemic weakened the influence of career motivation on interest in taking accounting profession education (PPAk). Keywords: Cost of education; Career Motivation; COVID-19 Pandemic; Student Interest